2020
DOI: 10.3897/phytokeys.164.56612
|View full text |Cite
|
Sign up to set email alerts
|

A new synonym from Hawaii and lectotypification of Plagiothecium longisetum (Plagiotheciaceae)

Abstract: Plagiothecium mauiense was first described in 1927 by V.F. Brotherus, based on materials from Hawaii. It has, so far been, treated as a separate species. A detailed analysis of the original material housed in the New York Botanical Garden Herbarium (NY01256708) found the specimen to be characterised by a lack of metallic lustre; concave, asymmetrical, lanceolate to lanceolate-ovate leaves, shrunken in their dry condition; a straight, not denticulate, acute to apiculate apex; elongate-hexagonal cells in irregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…However, this now appears possible and is the purpose of the present paper. Wolski and Proćków (2020) confirmed that syntypes of P. mauiense are deposited in four American herbaria: Harvard University Herbarium (FH00220142), Miami University Herbarium (MU 000000546), New York Botanical Garden Herbarium (NY01256708) and Yale University Herbarium (YU 233890). Although it was possible to take on loan the described material from only two of them (Herbaria NY and YU), all four herbaria were able to provide the necessary assistance, as well as a wealth of data, including microscopic photographs of the described original material.…”
Section: Introductionsupporting
confidence: 56%
“…However, this now appears possible and is the purpose of the present paper. Wolski and Proćków (2020) confirmed that syntypes of P. mauiense are deposited in four American herbaria: Harvard University Herbarium (FH00220142), Miami University Herbarium (MU 000000546), New York Botanical Garden Herbarium (NY01256708) and Yale University Herbarium (YU 233890). Although it was possible to take on loan the described material from only two of them (Herbaria NY and YU), all four herbaria were able to provide the necessary assistance, as well as a wealth of data, including microscopic photographs of the described original material.…”
Section: Introductionsupporting
confidence: 56%
“… Wolski and Proćków (2020) confirmed that syntypes of P. mauiense are deposited in four American herbaria: Harvard University Herbarium (FH00220142), Miami University Herbarium (MU 000000546), New York Botanical Garden Herbarium (NY01256708) and Yale University Herbarium (YU 233890). Although it was possible to take on loan the described material from only two of them (Herbaria NY and YU), all four herbaria were able to provide the necessary assistance, as well as a wealth of data, including microscopic photographs of the described original material.…”
Section: Introductionsupporting
confidence: 56%
“…A detailed comparative taxonomic analysis of the qualitative and quantitative features of the original material confirmed that the name is synonymous with P. longisetum Lindb. Additionally, the conducted research found all original specimens of P. mauiense to be syntypes ( Wolski and Proćków 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, to date, it was not possible to compare all known original material, so the lectotypification of P. mauiense was not completed (Wolski and Proćków 2020). However, this now appears possible and is the purpose of the present paper.…”
Section: Introductionmentioning
confidence: 99%